Relieving Burnout through Job Design: A SEM Approach - Anjali Jindal, Anjalijindal; Agarwal, Shivani (Ingeniería Solidaria, 2022)
Introduction: The research paper “Alleviating Burnout through Job Design: A SEM Approach”, was developed at KIET School of Management, KIET Group of Institutions in the year 2021. The challenges of the 21st century are to create a new paradigm that will lead to the success of an organization; one which must be decided by the organization itself. It is assumed that pay at the workplace is the most important factor for motivation. Problem: This paper proposes essentiality of the well-defined job design in such a manner, that the burnout must be reduced and further the employees’ performance can be enhanced. It will in turn help the organization effectively compete in the ever-challenging global market. Objective: Investigating the relation between job design and burnout in employees (managers) in FMCG companies. It’s done by assessment of changes in core dimensions of burnout with respect to Job Design. Design/Methodology/Approach: The assessment was done among 350 managers working in FMCG companies in Delhi/NCR. They had been given questionnaires to make assessment of the dimensions of different variables related to burnout. The hypothesis was made that job design and burnout have a negative correlation. Path analysis method was used to generate the model and got tested for job design and burnout. For the analysis of the obtained model SEM software AMOS 20.0 version was used. Conclusion: Sub hypotheses were formed by transforming the hypothesis. The hypotheses were validated by the results obtained from the analysis. It also substantiated that job design and burnout are negatively correlated significantly. Originality: The main aspect of this research was to examine the connection amongst these two variables i.e. job design and burnout. The resolve of this research is to examine the significant effect of job design in the alleviation of burnout. The major outcomes of the present research divulge that there is a negative and noteworthy association among job design and burnout. Restrictions: The correlation has only been validated amongst a limited setup of FMCG managers which gives a conceptual base. It can further be extended to other sectors of public and private companies and to other job roles and services. Various measures of management of employees can further be identified on the basis of this research finding to alleviate burnout. Originalidad: el propósito principal de esta investigación fue examinar la conexión entre estas dos variables, es decir, el diseño de puestos de trabajo y el agotamiento.